Using digital technology to improve the experience and quality of life in Malaysia's people's housing programme (PPR) through a maqasid shariah approach - Alias, Zuraini; Abdol Ghani, Mohd Reza; Saad, Mazni; Abdullah, Mokhtar; Mohammed Mohan, Noor Malinda (2025)
Malaysia's people's housing programme (PPR) was introduced to address the critical housing needs of the B40 income group, which comprises the bottom 40% of Malaysian households in terms of income, typically earning less than RM4,850 per month. This group often faces economic vulnerability, limited access to stable employment, and struggles to meet basic needs, such as food, healthcare, and housing. However, many residents continue to face persistent challenges, including environmental hazards, behavioural concerns, and safety issues - all of which affect their overall quality of life (QoL). These issues highlight the need for a more holistic approach to public housing that goes beyond infrastructure to also address social and environmental consciousness. A quantitative survey was conducted with 704 residents across five states, and the data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings indicate that the housing environment plays a significant role in shaping residents' attitudes and their overall living experience, both of which influence their QoL. Attitude serves as a strong mediating factor, underscoring how positive perceptions and behaviours can enhance engagement with the environment. Digital tools such as cleanliness-monitoring apps, safety alert platforms, and community engagement applications have the potential to improve not only physical conditions but also behavioural norms and lived experiences. When guided by Maqasid Sharian principles, these digital solutions offer a holistic, ethically grounded approach to enhancing dignity, well-being, and sustainable living for low-income urban populations.